2014
DOI: 10.4236/cellbio.2014.31003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Cultivation of Donor Mesenchymal Stromal Cells for Clinical Use in Cellular Therapy

Abstract: Mesenchymal stromal cells (MSC) have shown their benefits in graft-versus-host disease (GVHD), with five unsettled matters: 1) MSCs expansion in medium with Fetal Bovine Serum (FBS) and its risk of xenoreaction;2) The number of cells indicated for therapy that is relatively high, with the need to optimize the expansion, number and time wise; 3) The utilization of third party donors; 4) Culture passage number (P); and 5) Source of the cells. This study was designed to determine the superiority of the Platelet L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The mesenchymal cells were obtained from a bag and filter from bone marrow donors at the Hospital de Clínicas de Porto Alegre, used in hematopoietic stem cell transplantation, after the consent had been signed. Such procedures have no influence on this type of transplantation and studies have previously shown that it is possible to obtain these cells for cell therapy, with the advantage that this material aggregates the marrow donor serology data [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesenchymal cells were obtained from a bag and filter from bone marrow donors at the Hospital de Clínicas de Porto Alegre, used in hematopoietic stem cell transplantation, after the consent had been signed. Such procedures have no influence on this type of transplantation and studies have previously shown that it is possible to obtain these cells for cell therapy, with the advantage that this material aggregates the marrow donor serology data [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a substitute for BFS, human serum has been used successfully through platelet lysate (LP). In vitro studies have shown LP to be as effective as BFS for the expansion of MSC [ 22 , 23 ], and another study showed an expansion of mesenchymal stem cells cultured with LP 3.75 times greater than BFS [ 21 ]. Therefore, LP is safer from a biological point of view and is at least as efficient as BFS for cell expansion.…”
Section: Methodsmentioning
confidence: 99%
“…The product was prepared under Good manufacturing practices (GMP) conditions, based on the method described elsewhere. 13 Briefly, each batch consisted of platelet concentrate bags of a median of six donors (5-8 range), which were obtained from the blood bank immediately after their expiration time, having been previously irradiated at 25 Gray (Gy) during a cycle of 15 min. 24 The bags were frozen at −80°C overnight and thawed at 37°C; this cycle was repeated five times to ensure optimal platelet lysis.…”
Section: Platelet Lysate Preparationmentioning
confidence: 99%
“…[8][9][10][11] In mesenchymal stromal cells (MSC) culture, for example, it enhances proliferation, promoting the attainment of higher cell numbers in a shorter period. [12][13][14] This occurs because when activated in vivo, platelets undergo degranulation, releasing coagulation factors, adhesion molecules, growth factors, immune-related molecules, chemokines, and several other substances, which are either soluble or inside granules. [15][16][17] Microparticles constitute an efficient transport system of biomolecules and can be the main effectors of hPL activity in the in vitro cell culture's context.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, MSC isolation is limited to cell culture techniques such as plastic adhesion. This procedure involves a certain degree of in vitro manipulation and cell expansion [21,22]. Importantly, a small proportion of freshly isolated human MSCs acquire chromosomal abnormalities at early passages (0-4) of cultivation [23].…”
Section: Msc-derived Tumorsmentioning
confidence: 99%